Lifespan cost analysis of alternatives to global sulphur emission limit with uncertainties. (November 2021) - Huang, Daozheng; Hua, Yimin; Loughney, Sean; Blanco-Davis, Eduardo; Wang, Jin
Following the updated global sulphur emission cap from 1 January 2020, shipowners are facing an increasing cost burden to comply with the new regulation in a tough shipping market. This research compares the lifespan costs of three main alternatives, all of which can satisfy the 2020 global sulphur emission regulation. A lifespan cost analysis model is built considering several cost items across the three alternatives, including the initial cost of investment, maintenance cost and fuel consumption cost. Two vessels with a capacity of 5000 and 10, 000 TEUs are selected as case study vessels. The @risk software is utilized to conduct an uncertainty analysis with respect to the fuel price and the discount rate to test the three alternatives in different circumstances. The results indicate that the larger the vessel, the lower the discount rate, and the greater the price of Mixed Fuel Oil (a mixture of Very Low Sulphur Oil and Marine Gas Oil), the more attractive the scrubber option. Quantitatively, if the refining technology of low-sulphur fuel improves in the future and the price differential between Mixed Fuel Oil and Heavy Sulphur Fuel Oil decreases to 29 per ton for the 5000 TEU vessel or 27 per ton for the 10, 000 TEU vessel, the fuel-switch alternative will be as competitive as the use of a scrubber in terms of the lifespan cost. Additionally, as the discount rate increases, the cost gap between the use of a scrubber and the other two alternatives gradually decreases.